SEASONAL VARIATION IN DISTRIBUTION AND ABUNDANCE OF MOSQUITOES (DIPTERA: CULICIDAE) IN AKURE, NORTH LOCAL GOVERNMENT AREA, ONDO STATE, NIGERIA - JOSEPH, AFOLABI, OLAJIDE; COMFORT, ALADESANMI, OMOLOLA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2018)
The distribution and abundance of mosquito species in relation to seasons and habitats were studied between January, 2016 to December, 2017. One hundred and twenty sampling sites randomly distributed across six geographical locations of Akure North Local Government Area were sampled. The larvae collected were preserved in 70% ethanol and identified to species level. Evaluation of mosquito breeding sites revealed that concrete gutters harbored the largest number of mosquito larvae (1702) while the least number of mosquito larvae (127) was obtained from drum. Similarly, the highest relative abundance of mosquito larvae (98.44) was found in Shasha Market where 80% of the 20 sampled sites were positive for mosquito breeding. This abundance strongly correlated with highest temperature of 28°C, dissolved oxygen (7.69 mg/l), conductivity (85.25µs) and low alkaline (7.43). Meanwhile, the lowest relative abundance (20) correlated with lowest dissolved oxygen (6.55 mg/l) and relatively low temperature (27.48°C). Seasonal abundance of mosquito during the rainy season (88.80) was observed to be significantly higher than that of dry season (11.20). It was further observed that Ae. irritans, Ae. durbanensis, Ae. metallicus, Ae. amaltheus, Ae. vittastus, Cx. stratipes, Cx. nebulosus, Cx. horridus, Cx. philipi, Cx. stellatus, Cx. macfei, Cx. pruina and An. gambiae were completely absent in the study during the dry season. Even among the species that were present in both seasons with the exception of Cx. arbeeni, the percentage abundant was significantly higher in the rainy season than in the dry season. The persistent occurrence of Aedes, Culex and Anopheles species poses a serious epidemiological concern to the inhabitants of the study area since these mosquito genera are known vectors of diseases such as malaria, yellow fever and filariasis. Therefore, intensive vector control programs that are ecofriendly are recommended in order to reduce mosquito population and the prevalence of mosquito-borne diseases in the study area.